Individualized versus Fixed Positive End-expiratory Pressure for Intraoperative Mechanical Ventilation in Obese Patients: A Secondary Analysis. (June 2021) - Simon, Philipp; Girrbach, Felix; Petroff, David; Schliewe, Nadja; Hempel, Gunther; Lange, Mirko; Bluth, Thomas; Gama de Abreu, Marcelo; Beda, Alessandro; Schultz, Marcus J.; Pelosi, Paolo; Reske, Andreas W.; et al.
Abstract : Background: General anesthesia may cause atelectasis and deterioration in oxygenation in obese patients. The authors hypothesized that individualized positive end-expiratory pressure (PEEP) improves intraoperative oxygenation and ventilation distribution compared to fixed PEEP. Methods: This secondary analysis included all obese patients recruited at University Hospital of Leipzig from the multicenter Protective Intraoperative Ventilation with Higher versus Lower Levels of Positive End-Expiratory Pressure in Obese Patients (PROBESE) trial (n = 42) and likewise all obese patients from a local single-center trial (n = 54). Inclusion criteria for both trials were elective laparoscopic abdominal surgery, body mass index greater than or equal to 35 kg/m 2, and Assess Respiratory Risk in Surgical Patients in Catalonia (ARISCAT) score greater than or equal to 26. Patients were randomized to PEEP of 4 cm H2 O (n = 19) or a recruitment maneuver followed by PEEP of 12 cm H2 O (n = 21) in the PROBESE study. In the single-center study, they were randomized to PEEP of 5 cm H2 O (n = 25) or a recruitment maneuver followed by individualized PEEP (n = 25) determined by electrical impedance tomography. Primary endpoint was PaO2 /inspiratory oxygen fraction before extubation and secondary endpoints included intraoperative tidal volume distribution to dependent lung and driving pressure. Results: Ninety patients were evaluated in three groups after combining the two lower PEEP groups. Median individualized PEEP was 18 (interquartile range, 16 to 22; range, 10 to 26) cm H2 O. PaO2 /inspiratory oxygen fraction before extubation was 515 (individual PEEP), 370 (fixed PEEP of 12 cm H2 O), and 305 (fixed PEEP of 4 to 5 cm H2 O) mmHg (difference to individualized PEEP, 145; 95% CI, 91 to 200; P < 0.001 for fixed PEEP of 12 cm H2 O and 210; 95% CI, 164 to 257; P < 0.001 for fixed PEEP of 4 to 5 cm H2 O). Intraoperative tidal volume in the dependent lung areas was 43.9% (individualized PEEP), 25.9% (fixed PEEP of 12 cm H2 O) and 26.8% (fixed PEEP of 4 to 5 cm H2 O) (difference to individualized PEEP: 18.0%; 95% CI, 8.0 to 20.7; P < 0.001 for fixed PEEP of 12 cm H2 O and 17.1%; 95% CI, 10.0 to 20.6; P < 0.001 for fixed PEEP of 4 to 5 cm H2 O). Mean intraoperative driving pressure was 9.8 cm H2 O (individualized PEEP), 14.4 cm H2 O (fixed PEEP of 12 cm H2 O), and 18.8 cm H2 O (fixed PEEP of 4 to 5 cm H2 O), P < 0.001. Conclusions: This secondary analysis of obese patients undergoing laparoscopic surgery found better oxygenation, lower driving pressures, and redistribution of ventilation toward dependent lung areas measured by electrical impedance tomography using individualized PEEP. The impact on patient outcome remains unclear. Abstract : Individualized positive end-expiratory pressure (PEEP; median 18 cm H2 0) was superior to either fixed low levels (4 to 5 cm H2 0) or a higher level (12 cm H2 0 with recruitment) with regards to oxygenation, driving pressures, and indices of regional ventilation. Despite improvement in lung function, no differences in postoperative pulmonary complications were observed. However, this cohort was not adequately powered for clinical outcomes.Supplemental Digital Content is available in the text.